Pattern of surgical patients admitted into a unit of surgery department of Rangpur Medical College Hospital, Bangladesh (The Planet, 2021)
Introduction: Although Bangladesh is included in the medium human development category,the people of densely populated Rangpur division are very poor due to unemployment of a largenumber landless farmers and labours. They are illiterate and of ill-health. Aims andObjectives: This study aimed to show the pattern of patients admitted in a surgery unit ofRangpur Medical College Hospital and to correlate surgical diseases to their age and sex.Methods and materials: This cross sectional study was done in a surgery unit of RangpurMedical College Hospital. Total 450 admitted patients were randomly selected from thedischarge book of unit during the period of June, 2019 to December, 2019. Patients withincomplete information were omitted. Results: Among the patients, 29 were male and 157were female. Majority of them (27.5%) were of age group 25- 34 years followed by age group35-44 (22.4%), 45- 54 (18.6%) and then others. Majority of patients with appendicitis andappnedicular lumps were in between 15 to 44 years. Females suffered more (69.2%) withbiliary diseases than males (30.8%). Also, females suffered from cholelitihasis (56.4%) morethan thrice the males (15.4%). Conclusion: Majority of patients were of cases of physicalassaults followed by RTA, appendicitis and appendicular lump, biliary diseases, hernia &hydrocele and then others.
Keywords: Monga; UTI; Cholelithiasis; Abscess; Hydrocele; Hernia